2017
DOI: 10.1590/s0102-865020170108
|View full text |Cite
|
Sign up to set email alerts
|

Claudin-3 and occludin content in the glands of colonic mucosa devoid from fecal stream submitted to topical intervention with oil extract of Curcuma longa

Abstract: 1 8-Experimental SurgeryActa Cir Bras. 2017;32(1):65-73 AbstractPurpose: To evaluate the inflammatory intensity and measure the tissue content of the proteins claudin-3 and occludin in the colonic mucosa without fecal stream submit to intervention with curcumin. Methods: Thirty-six rats were submitted to a proximal colostomy and a distal mucous fistula and divided into two groups according to sacrifice to be performed two or four weeks. Each group was divided into three subgroups according daily application of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 36 publications
2
12
0
10
Order By: Relevance
“…59 Consistent with the data from our laboratory, Martinez et al showed that curcumin preserves the tissue content of claudin-3 and occludin in the colonic mucosa. 60 Tian et al also proposed that curcumin protects the intestine from ischemia/reperfusion injury through restoration of the epithelial structure, promotion of the recovery of intestinal permeability, as well as enhancement of ZO-1 protein expression. 61 Collectively, these data provide strong evidence for curcumin-mediated beneficial modulation of the layer 3 of the intestinal barrier.…”
Section: Layer 3 or The Epitheliummentioning
confidence: 99%
“…59 Consistent with the data from our laboratory, Martinez et al showed that curcumin preserves the tissue content of claudin-3 and occludin in the colonic mucosa. 60 Tian et al also proposed that curcumin protects the intestine from ischemia/reperfusion injury through restoration of the epithelial structure, promotion of the recovery of intestinal permeability, as well as enhancement of ZO-1 protein expression. 61 Collectively, these data provide strong evidence for curcumin-mediated beneficial modulation of the layer 3 of the intestinal barrier.…”
Section: Layer 3 or The Epitheliummentioning
confidence: 99%
“…Os RLO, em especial o hidroxil (OH), são radicais tóxicos para as diferentes estruturas lipoproteicas das células que formam o epitélio intestinal. O estresse oxidativo resultante da maior produção de RLO, danifica diferentes estruturas celulares e, entre elas, as proteínas que constituem os sistemas de adesão intercelular 1,12,18,19,26,28 . Já se demonstrou que o estresse oxidativo destrói várias proteínas que formam a barreira epitelial da mucosa, representadas pela camada de muco, membrana citoplasmática, junções intercelulares e membrana basal 8,12,17,23 .…”
Section: Discussionunclassified
“…O epitélio intestinal é formado por uma única camada de células com propriedades absortivas, intimamente aderidas entre si e à membrana basal 12,17,18,23 . A união das células epiteliais ocorre graças a sistemas de junções célula-célula, os quais suportam grande parte do estresse mecânico sobre a parede intestinal 5 .…”
Section: Discussionunclassified
See 2 more Smart Citations